تغيرات سطح القرنية الأمامي ودورها في الخطأ الانكساري التالي لجراحة الساد بالفاكو - رجب, محمود; جلول, قحطان; إبراهيم, ديار (Latakia University Journal -Medical Sciences Series, 2015)
أجريت الدراسة على (50) عين لـ (50) مريض من مراجعي قسم أمراض العين وجراحتها في مشفى الأسد الجامعي باللاذقية في الفترة الممتدة من تشرين الثاني 2012 حتى تشرين الثاني 2013, منهم 32 (64%) ذكراً و 18 (36%) أنثى لديهم ساد شيخي، بمتوسط عمري (59.88±7.24 سنة) بهدف دراسة تغيرات سطح القرنية الأمامي بعد جراحة استحلاب العدسة بالأمواج فوق الصوتية (الفاكو) ودور هذه التغيرات في الخطأ الانكساري التالي للجراحة. تمت متابعة المرضى خلال ثلاثة أشهر وبفترات منتظمة بعد إجراء الجراحة وفي كل زيارة كان يتم تسجيل أفضل قدرة بصرية مصححة وقوة تحدب القرنية الأفقية والعمودية والخطأ الانكساري الكروي واللابؤري بواسطة جهاز (Grand Seiko GRK-1 Auto Kerato-Refractometer) في استمارة خاصة بكل مريض. أظهرت النتائج تطور أفضل قدرة بصرية مصححة من (0.27±0.1) قبل الجراحة إلى (0.92±0.16) بعد الجراحة بثلاثة أشهر. كما تبين حدوث تحدب غير هام إحصائياً في المحور الأفقي للقرنية (0.12 كسيرة) (0.13P=)، وتسطح هام في المحور العمودي (0.21 كسيرة) (P=0.0001)، وتسطح غير هام إحصائياً في قوة تحدب القرنية الوسطية (0.05 كسيرة) P=0.215)) وذلك بعد ثلاثة أشهر من الجراحة في حين أن الخطأ الانكساري الكروي بعد الجراحة بثلاثة أشهر كان حوالي (0.24±0.93) كسيرة. كانت اللابؤرية الانكسارية التالية للجراحة حوالي (-0.74±1.08) كسيرة واللابؤرية القرنية حوالي (1.18±0.63) كسيرة وقد تبين عدم وجود فرق هام إحصائياً بينهما (P=0.61). كانت اللابؤرية القرنية المحدثة بالجراحة SIA حوالي (±0.470.38) كسيرة وقد تبين عدم وجود فرق هام إحصائياً بين اللابؤرية القرنية قبل وبعد الجراحة(P=0.785) وبذلك يمكننا القول إن تغيرات سطح القرنية الأمامي بعد جراحة الساد بالفاكو مسؤولة عن (20.83%) من الخطأ الانكساري الكروي التالي للجراحة كما أن اللابؤرية القرنية التالية للجراحة تفسر اللابؤرية الانكسارية في حوالي (76%) من الحالات واللابؤرية القرنية المحدثة بالجراحة مسؤولة عن (67%) من اللابؤرية الانكسارية المحدثة بالجراحة. The study was performed on (50) eyes of (50) patients who attended the Ophthalmology Department at Al-Assad Hospital University in Lattakia, from Nov 2012 to Nov 2013. Our study included 32 (64%) males and 18 (36%) females who had senile cataract with mean age about (59.88±7.24 years). The aim was to study anterior corneal surface changes after phacoemulsification and the role of these changes in the refractive error after surgery. The patients were followed by regular periods during three months after surgery. In each visit, we recorded Best Correct Visual Acuity (BCVA), vertical, horizontal keratometry reading (K-reading) and sphere and astigmatic refraction errorby (Grand Seiko GRK-1 Auto Kerato-Refractometer) in a private data sheet for each patient. Results showed improving in BCVA from (0.27±0.1) before surgery to (0.92±0.16) three months after surgery. There was no significantstatistical value in steepening of horizontal meridian (0.12)D (P=0.13),but significant flattening in vertical meridian (0.21)D (P=0.0001), with no significant flattening in mean keratometric reading (0.05)D (P=0.215) three months after surgery. The mean of spherical refraction error after three months of surgery was (0.24±0.93)D. The refractive astigmatism after surgery was about (-1.08±0.74)D, and the keratometric astigmatism about (1.18±0.63)D, there was no significant difference between them(P=0.61).The Surgically Induced Astigmatism ( SIA) was about (0.47±0.38)D. There was no significant statistical value according to the keratometric astigmatism before and after surgery(P=0.785). So, we can say that the anterior corneal surface changes after phacoemulsification are responsible for (20.83%) of the spherical refractive error after surgery. The corneal astigmatism after surgery is interpreting the refractive astigmatism in about (76%) of patients and SIA is responsible for about (67%) of surgery induced refractive astigmatism.